2020
DOI: 10.19044/ejes.v7no2a6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bullying and Cyberbullying Among Urban Middle School Students

Abstract: This study examined bullying and cyberbullying among 185 middle school students in 4 urban middle schools in Ohio. Nearly 60% of the sample was female, and 67% of the sample was not Caucasian. The results indicated that bullying and cyberbullying are prevalent in this population. Approximately 44% of 6 th -grade students felt terrible about themselves due to bullying, and 62% of all female students believed other students had spread false rumors about them. On average, female students reported more bullying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Another analysis, based on 63 studies ( Zhu et al, 2021 ), showed prevalence rates between 14.6% and 52.2% for bullying victimization and 6.3% to 32% for cyberbul-lying perpetration. According to Atkins et al (2020) , 39% of students reported experiencing cyberbullying. Kowalski et al (2014) found that 15% to 18% of adolescents had been cyberbullied, while the percentage of perpetrators ranged between 7 and 18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another analysis, based on 63 studies ( Zhu et al, 2021 ), showed prevalence rates between 14.6% and 52.2% for bullying victimization and 6.3% to 32% for cyberbul-lying perpetration. According to Atkins et al (2020) , 39% of students reported experiencing cyberbullying. Kowalski et al (2014) found that 15% to 18% of adolescents had been cyberbullied, while the percentage of perpetrators ranged between 7 and 18.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here had two major purposes. Firstly we wanted to determine the prevalence rates of cyberbullying in Polish adolescents, considering the fact that there were great discrepancies in rates reported in studies of other nations ( Atkins et al, 2020 ; Park et al, 2021 ). In order to cover the whole context of cyberbullying, we decided to include four types of respondents: bullies only; victims only; bully-victims; no bullies and no victims.…”
Section: Introductionmentioning
confidence: 99%